2005
DOI: 10.1055/s-2005-916278
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Colectomy for Colon Cancer: Comparable to Conventional Oncologic Surgery?

Abstract: As a result of the obvious benefits of laparoscopic cholecystectomy, minimally invasive techniques have been applied to more complex gastrointestinal procedures, including colorectal resections. The goal in adapting laparoscopic techniques for colorectal surgery is to offer an operation that results in less pain, shorter hospital stay, more rapid return to normal activities, and improved cosmesis compared with conventional operation. The challenge has been to show that this can be done safely and efficiently a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The introduction of minimally invasive techniques for colorectal surgerylaparoscopy and more recently robotics-has allowed surgeons to treat these conditions with smaller incisions, shortened hospital stays, less postoperative pain, and an often quicker return of bowel function and return to normal activity [1][2][3][4]. The use of the robotic platform also offers significant benefits to the surgeon including improved ergonomics, 3D visualization, endo-wrist maneuverability, and precision movements, especially when working in narrow spaces like the pelvis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The introduction of minimally invasive techniques for colorectal surgerylaparoscopy and more recently robotics-has allowed surgeons to treat these conditions with smaller incisions, shortened hospital stays, less postoperative pain, and an often quicker return of bowel function and return to normal activity [1][2][3][4]. The use of the robotic platform also offers significant benefits to the surgeon including improved ergonomics, 3D visualization, endo-wrist maneuverability, and precision movements, especially when working in narrow spaces like the pelvis.…”
mentioning
confidence: 99%
“…Each year, thousands of surgeries are performed in the USA to treat colorectal diseases such as colorectal cancer, ulcerative colitis, and diverticular disease [1,2]. The introduction of minimally invasive techniques for colorectal surgerylaparoscopy and more recently robotics-has allowed surgeons to treat these conditions with smaller incisions, shortened hospital stays, less postoperative pain, and an often quicker return of bowel function and return to normal activity [1][2][3][4].…”
mentioning
confidence: 99%
“…Several studies were conducted to elucidate the reason for this so high incidence 4 . In 2007 Fleshman et al, based on the COST study (tested with follow-up of five years), showed that there is no statistical difference in tumor recurrence in the surgical wound when comparing laparotomic or laparoscopic colectomy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…12,13 A suboptimal surgical approach may, therefore, potentially lead to understaging of advanced disease and contribute to poorer survival outcomes. 9 The feasibility of identifying and resecting peritoneal disease within multiple abdominal quadrants has been identified as a potential limitation of MIS, 14 and data evaluating the appropriateness of MIS in the management of type II ECs are limited. Finally, recognizing that, in some centers, adjuvant chemotherapy is omitted in noninvasive stage IA USC, inadequate staging may result in undertreatment.…”
mentioning
confidence: 99%